ANALISIS PERBEDAAN SELF ESTEEM, ACADEMIC SELF-EFFICACY, DAN MOTIVASI BELAJAR ANTAR TINGKAT SEMESTER PADA MAHASISWA STPK ST. YOHANES RASUL JAYAPURA - Angela Marciana Ayu Saptarina Maturbongs; Stefanus Lobya; Agnes Anggi Dian Winei (SOSCIED, 2026)
This study aims to examine differences in self-esteem, academic self-efficacy, and learning motivation across semesters among students at St. John the Apostle School of Pastoral Catechetics in Jayapura. A quantitative approach with a comparative design was applied to 68 students from a population of 171. Data were collected cross-sectionally using the Rosenberg Self-Esteem Scale (RSES), a general academic self-efficacy scale, a learning motivation scale, and records of the Cumulative Grade Point Average (CGPA). Data analysis included item validity testing, Cronbach’s alpha reliability, exploratory factor analysis to examine the structure of the RSES, one-way analysis of variance, the Kruskal-Wallis test, and Bayes factor analysis to evaluate the null hypothesis. The results showed that the RSES was divided into two uncorrelated dimensions (r = −0.007), namely Negative Self-Esteem and Positive Self-Esteem. Significant differences across semesters were found only in the Negative Self-Esteem dimension (p = 0.008), where senior students exhibited a lower tendency toward self-deprecation compared to students in their first semesters. Conversely, the Positive Self-Esteem dimension, total RSES scores, academic self-efficacy, and learning motivation showed no differences. Bayesian factor analysis provided very strong evidence (BF₀₁ > 100) supporting the absence of differences in self-efficacy and learning motivation, indicating that these null findings reflect the true state of affairs. Psychological interventions should focus on managing self-doubt, particularly among first-year students.